Constructing frontiers between Judaism and Christianity in the Roman Empire: the Judaizers and anti-Jewish rhetoric in the Christian movement of the centuries I and II AD - Selvatici, Monica (Romanitas - Revista de Estudos Grecolatinos, 2013)
The purpose of this article is to analyze the anti-Jewish rhetoric in 1st and 2nd century CE through the Christian texts. Such rhetoric is not fostered by Jewish attacks against Christian faith, but, differently, by the constant presence of Christian Judaizers (those who used to follow Jewish commandments not observed by the majority of Christians anymore). It helps to construct frontiers between Christians and Jews and to craft Christian identity as something opposed to the realm of Jewish customs and practices.
Keywords: Christianity; Judaism; Frontiers; Anti-Jewish rhetoric